The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/02109395.2021.1950462
|View full text |Cite
|
Sign up to set email alerts
|

Does compliance with the preventive health behaviours against COVID-19 mitigate the effects of depression, anxiety and stress? (¿Cumplir con los comportamientos preventivos de salud contra el COVID-19 reduce los efectos de la depresión, la ansiedad y el estrés?)

Abstract: In the present study, the aim was to investigate the associations between compliance with preventive health behaviours, depression, anxiety and stress. 478 adults living in Turkey voluntarily filled out the online survey, which comprised demographic questions, Measure of Compliance with Preventive Health Behaviours against COVID-19, and Depression Anxiety Stress Scales, between 24-31 March 2020: during the initial phase of the COVID-19 pandemic in Turkey. Results revealed that compliance with preventive health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(212 reference statements)
0
4
0
1
Order By: Relevance
“…First, this was a cross‐sectional study since the KCHS was conducted by selecting new participants in each wave; thus, any causal relationships are unclear. One prior study showed that non‐compliance with preventive behaviors may increase depression 63 . Therefore, further longitudinal studies are required to confirm any causal relationships between depression and COVID‐19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this was a cross‐sectional study since the KCHS was conducted by selecting new participants in each wave; thus, any causal relationships are unclear. One prior study showed that non‐compliance with preventive behaviors may increase depression 63 . Therefore, further longitudinal studies are required to confirm any causal relationships between depression and COVID‐19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…One prior study showed that non-compliance with preventive behaviors may increase depression. 63 Therefore, further longitudinal studies are required to confirm any causal relationships between depression and COVID-19 preventive behaviors. Second, there might be a social desirability bias because compliance with preventive behaviors was evaluated using a self-reported questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, role ambiguity and absence of precise information regarding work goals leads to increased stress and weakened satisfaction (Cordes & Dougherty, 1993). Employees whose roles and responsibilities are not clear may not engage in creative initiatives (Aydin & Kaya, 2021;Dou et al, 2022). Evidence also indicates that teams which are exposed to stressors are less likely to perform creatively (Razinskas et al, 2022).…”
Section: Relating Hindrance Stressors With Creativity and Burnoutmentioning
confidence: 99%
“…En este sentido, la ambigüedad de la función laboral y la ausencia de información precisa sobre las metas laborales producen un mayor nivel de estrés y menor nivel de satisfacción (Cordes & Dougherty, 1993). Los trabajadores cuya posición y responsabilidades no están definidas con claridad tienden a no participar en iniciativas creativas (Aydin & Kaya, 2021;Dou et al, 2022). La evidencia sugiere que los equipos que están expuestos a estresores son menos tendentes a desenvolverse con creatividad (Razinskas et al, 2022).…”
Section: La Vinculación De Los Estresores Obstáculo Con La Creativida...unclassified
“…Various factors were contributing to the panic atmosphere that started immediately after the first news about the health crisis (Nicomedes & Avila, 2020). Some of them were (1) the high transmission efficacy of the virus via asymptomatic individuals (Aydin & Kaya, 2021; Zhang et al, 2021), (2) limited knowledge regarding the nature, severity, and effects of the virus (Koh, Shah, et al, 2020; W. Zhang & Qian, 2020), (3) absence of approved pharmacological and medical solutions for the coronavirus infection at the time of beginning phase (Alvi et al, 2020; Sanders et al, 2020), and (4) mistrust in the formal sources of information regarding the origin and severity of the virus (Breakwell & Jaspal, 2021; Simione et al, 2021). Therefore, most of the systems shattered due to the unpreparedness of society for a sudden emergence of such a global crisis engulfing the economy, healthcare, logistics, education, business, and everyday life (Altig et al, 2020; Donthu & Gustafsson, 2020; Kapasia et al, 2020; Leung et al, 2021; Singh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%